Analisis Segmentasi untuk Menentukan Kebutuhan Sumber Daya Manusia Di Bidang Tenaga Kerja Outsourcing Industri Pengiriman dengan Menggunakan Metode K-MEANS - Ganang Kartiko Aji; Ahmad Ilham Bachrie Harahap; Mufti Kusuma Firdaus; Jerry Heikal (IPM2KPE, 2025)
This study aims to identify the segmentation of outsourced workforce needs in the shipping industry to support a more effective recruitment strategy at PT FOC Indonesia. The research method used is K-Means Clustering, with a secondary data analysis approach from 120 workers categorized by age, marital status, job title, and country of employment. The results indicate seven main workforce clusters, each representing specific personas such as Experienced Captains, Engineers, and Electrical Specialists, as well as market preferences such as Korea, Japan, and China. The conclusion of this study is that data-driven workforce segmentation can assist companies in developing recruitment strategies, reducing turnover, and increasing the efficiency and competitiveness of the Indonesian workforce in the global market. Keywords: K-Means, Workforce Segmentation, Shipping Industry, Outsourcing, Manning Agency